Optical Properties of GaN Thin Flim - Shaban, Salma M. (Iraqi Journal of Physics, 2009)
GaN thin films were deposited by thermal evaporation onto glass substrates at substrate temperature of 403 K and a thickness of 385 nm . GaN films have amorphous structure as shown in X-ray diffraction pattern . From absorbance data within the range ( 200- 900 ) nm direct optical energy gap was calculated . Also the others optical parameters like transmittance T, reflectance R , refractive index n , extinction coefficient k , real dielectric constant 1 Î , and imaginary dielectric constant 2 Î were determined . GaN films have good absorbance and minimum transmittance in the region of the visible light .